2009
DOI: 10.2105/ajph.2009.174557
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships for Environmental and Occupational Justice: Contributions to Research, Capacity and Public Health

Abstract: In 1994, the National Institute of Environmental Health Sciences (NIEHS) initiated a program to address communication gaps between community residents, researchers and health care providers in the context of disproportionate environmental exposures. Over 13 years, together with the Environmental Protection Agency and National Institute for Occupational Health and Safety, NIEHS funded 54 environmental justice projects. Here we examine the methods used and outcomes produced based on data gathered from summaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…This may mark a significant shift in programs to increase EHL moving forward, towards closer alignment with approaches such as community-based participatory research (CBPR), which state community action grounded in research findings as an explicit goal [74]. Although many studies have successfully used qualitative and community-based research methods to elucidate the more complex and dynamic factors influencing environmental health, including social factors, these methods remain underrepresented in the environmental health field [75,76]. …”
Section: Discussionmentioning
confidence: 99%
“…This may mark a significant shift in programs to increase EHL moving forward, towards closer alignment with approaches such as community-based participatory research (CBPR), which state community action grounded in research findings as an explicit goal [74]. Although many studies have successfully used qualitative and community-based research methods to elucidate the more complex and dynamic factors influencing environmental health, including social factors, these methods remain underrepresented in the environmental health field [75,76]. …”
Section: Discussionmentioning
confidence: 99%
“…Cohen et al 2012; Brown et al 2012; Minkler et al 2008). CBPR has been used widely and NIEHS has been funding projects integrating CBPR practices since the late 1990s (though NIEHS did not start using the term CBPR until 2000), initially through its Environmental Justice and CBPR programs, and more recently through it Partnerships in Environmental Public Health program (Brown et al 2012; Baron et al 2009; O’Fallon and Dearry, 2002; O’Fallon and Dearry, 2002;). In spirit, CBPR shares much with popular epidemiology (Table 1).…”
Section: 0 Participatory Approachesmentioning
confidence: 99%
“…As a case in point, between 1994 and 2007, under the “Partnerships for Communication” program, NIEHS, National Institute for Occupational Safety and Health and USEPA funded a total of 54 projects and 27 were led by community-based organizations. These grants required the collaboration of multiple partners, and based upon program evaluations, these projects increased environmental health literacy by raising community awareness, building community capacity, improving community health behaviors, and reducing exposures (Baron et al 2009). …”
Section: 0 Conclusionmentioning
confidence: 99%
“…In other situations that pose potential environmental health risks to local populations, community participation in research planning has been identified as key to reducing conflict, informing effective outreach, and conducting effective research (2528). The growth of community-based participatory research (CBPR) in the area of environmental health reflects an increasing recognition that communities should be involved in all phases of environmental health research (29).…”
Section: Implications For a Community-informed Health Research Agendamentioning
confidence: 99%
“…The growth of community-based participatory research (CBPR) in the area of environmental health reflects an increasing recognition that communities should be involved in all phases of environmental health research (29). Scholars and communities who engage in CBPR recognize that, in addition to involving residents in conducting research, it is also important to provide for community involvement in setting research agendas and framing key questions (28, 30, 31). Engaging communities in prioritizing and designing research helps assure that studies address communities' key concerns, utilize citizens' knowledge, account for local differences, and inform decision making processes.…”
Section: Implications For a Community-informed Health Research Agendamentioning
confidence: 99%